Glycemic control and vaccine response: the role of mucosal immunity after vaccination in diabetic patients - Mojaddidi, Moaz A.; Aboonq, Moutasem; Alqahtani, Saeed A. (Frontiers in Immunology, 2025)
This review explores the critical interplay between glycemic control, mucosal immunity, and vaccine response in diabetic patients. Diabetes mellitus, characterized by impaired glucose regulation, significantly impacts immune function, particularly at mucosal surfaces. Poor glycemic control diminishes vaccine-induced antibody responses and compromises mucosal defenses, such as secretory IgA production, increasing susceptibility to infections. We synthesize evidence highlighting the importance of optimizing glycemic management prior to vaccination to enhance immunogenicity. Furthermore, we examine the potential of personalized vaccination strategies, tailored to individual glycemic status, age, BMI, and kidney function, to improve vaccine efficacy in this vulnerable population. Additionally, we discuss the role of adjunct therapies, including probiotics, nutritional interventions, and lifestyle modifications, in modulating the gut microbiota and reinforcing mucosal barrier integrity. This review underscores the necessity for an interdisciplinary approach, integrating metabolic management with innovative vaccine designs, to maximize protection against infectious diseases in diabetic patients. Future research should prioritize longitudinal studies assessing both systemic and mucosal immunity and refine personalized vaccination strategies to ensure robust and durable protection.